The effect of digital eco-learning in student worksheet flipbook to environmental project literacy and pedagogic competency - Sumarmi Sumarmi; Muhammad Aliman; Tuti Mutia (OmniaScience, 2021)
The study aimed to determine 1) the effect of digital eco learning in student worksheet flipbooks on environmental literacy projects, and 2) the effect of digital eco learning in student worksheet flipbooks on student ecological competence. The research is a quasi-experimental study using a Pretest-Posttest Non-equivalent Control Group. The research subjects were students in the Environmental Geography course semester 6 of 2020, divided into the experimental and control groups. The research was conducted at the Geography Education study program, Social Science Faculty, State University of Malang, Indonesia. Data were analyzed using the independent sample t-test in SPSS version 23 for windows. The results found: 1) there is a significant effect of digital eco learning with student worksheet flipbook on environmental project literacy competence, and 2) there is a significant effect of digital eco learning with student worksheet flipbooks on ecological competence.